Hypoxia inducible factor 1α expression and effects of its inhibitors in canine lymphoma - KAMBAYASHI, Satoshi (J Vet Med Sci, 2015)
Hypoxic conditions in various cancers are believed to relate with their malignancy, and hypoxia inducible factor-1α (HIF-1α) has been shown to be a major regulator of the response to low oxygen. In this study, we examined HIF-1α expression in canine lymphoma using cell lines and clinical samples and found that these cells expressed HIF-1α. Moreover, the HIF-1α inhibitors, echinomycin, YC-1 and 2-methoxyestradiol, suppressed the proliferation of canine lymphoma cell lines. In a xenograft model using NOD/scid mice, echinomycin treatment resulted in a dose-dependent regression of the tumor. Our results suggest that HIF-1α contributes to the proliferation and/or survival of canine lymphoma cells. Therefore, HIF-1α inhibitors may be potential agents to treat canine lymphoma.